CARICOM Multi-Agency Health Family Life Education Project: Summary Report of Trinidad and Tobago Needs Assessment Study (Students 9-11 Years Old) - The University of the West Indies, Cave Hill, School of Education (School of Education, UWI, 1997)
The HFLE Needs Assessment Study was carried out to obtain data on student knowledge and views about health lifestyles, a range of psycho-social issues affecting youth, and some aspects of the modus-operandi of the existing HFLE curriculum. It also sought to explore the problems, concerns, and values of young people; possible goals, outcomes and teaching and assessment methods of HFLE; and factors affecting the teaching of HFLE. The intended respondents were students in primary and secondary schools, and their teachers, principals and parents. This report summarizes and discusses the responses of Trinidadian primary school students 9-11 years old. The students in this age group appear to have interpreted health as more than physical well-being. The majority of them thought that they could catch AIDS from normal classroom contact. The problems seen as causing the most hardships were unemployment, drug abuse, lack of education, and AIDS and STDs, in that order.
CARICOM Multi-Agency Health and Family Life Education Project
Keywords: health and family life education; HFLE